2017
DOI: 10.1016/j.ijid.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in serotypes of S. pneumoniae isolates causing invasive and non-invasive diseases in unvaccinated population in Mexico (2000-2014)

Abstract: A percentage of annual decline of serotypes causing IPD and NIPD included in PCV was detected among groups not targeted to receive the vaccine, probably due to herd effect. Considering pneumococcal serotype distribution is a dynamic process, we highlight the importance of surveillance programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 22 publications
0
10
0
2
Order By: Relevance
“…There are significant advantages of using lambs to model RSV infection as a correlate for human infants-including the ability to use human viral strains without adaptation and the similarity of the pathological sequelae [30,31]. Serotype 22F is thought to have appeared after the introduction of the S. pneumoniae vaccine PCV7 ( [44]). While this serotype was not widespread in those subsequent years ( [44]), 22F is now the second most common serotype causing invasive disease in children less than seven years old and the primary cause in the elderly [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant advantages of using lambs to model RSV infection as a correlate for human infants-including the ability to use human viral strains without adaptation and the similarity of the pathological sequelae [30,31]. Serotype 22F is thought to have appeared after the introduction of the S. pneumoniae vaccine PCV7 ( [44]). While this serotype was not widespread in those subsequent years ( [44]), 22F is now the second most common serotype causing invasive disease in children less than seven years old and the primary cause in the elderly [45].…”
Section: Discussionmentioning
confidence: 99%
“…Serotype 22F is thought to have appeared after the introduction of the S. pneumoniae vaccine PCV7 ( [44]). While this serotype was not widespread in those subsequent years ( [44]), 22F is now the second most common serotype causing invasive disease in children less than seven years old and the primary cause in the elderly [45]. Molecular analysis of this serotype also indicates six different lineages and 18% of clinical isolates demonstrating erythromycin resistance ( [19]).…”
Section: Discussionmentioning
confidence: 99%
“…There are significant advantages of using lambs to model RSV infection as a correlate for human infants -including the ability to use human viral strains without adaptation and the similarity of the pathological sequelae [24,25]. Serotype 22F is thought to have appeared after the introduction of the S. pneumoniae vaccine PCV7 ( [37]). While this serotype was not widespread in those subsequent years ( [37]), 22F is now the second most common serotype causing invasive disease in children less than seven years old and the primary cause in the elderly [38].…”
Section: Rsv Infection Of Lamb Phagocytes Are Permissivementioning
confidence: 99%
“…Serotype 22F is thought to have appeared after the introduction of the S. pneumoniae vaccine PCV7 ( [37]). While this serotype was not widespread in those subsequent years ( [37]), 22F is now the second most common serotype causing invasive disease in children less than seven years old and the primary cause in the elderly [38]. Molecular analysis of this serotype also indicates six different lineages and 18% of clinical isolates demonstrating erythromycin resistance ( [18]).…”
Section: Rsv Infection Of Lamb Phagocytes Are Permissivementioning
confidence: 99%
“…However, detection of emerging new serotypes in the late PCV7 period led to the inclusion of six additional serotypes in the new PCV13 in 2010. Since then, decreases in invasive pneumococcal disease (IPD), not only in children but also in adults due to herd effect [ 24 27 ], as well as in PCV13 serotypes involved in non-invasive diseases, have been described [ 25 , 27 ]. Although some studies [ 28 – 30 ], but not others [ 24 , 31 ], have found slight increases in non-PCV13 serotypes causing IPD, individually none of the non-PCV13 serotypes has shown a significant increase [ 32 ], in contrast to the increase in serotype 19A (with its associated resistant sequence types [ 33 ]) after PCV7 implementation [ 33 35 ].…”
Section: Pharmacoepidemiology Of Resistances In Human-adapted Respiramentioning
confidence: 99%